Perfil neuropsicológico y rasgos de personalidad en pacientes con adicción a las drogas - Guevara Castro, Nicole Anahí; Jurado Romero, Cristobal Alejandro (My University, 2024)
Addictions are complex disorders, where an individual is dependent on an action or substance, generating various problems in the daily life of the individual, both physiologically and neurologically, this is why we will analyze the neuropsychological profile, which is an evaluation with which you can analyze various neurological functions, such as attention, memory, visual perception, arithmetic skills, language, praxis and executive function, and on the other hand, personality, which is the set of characteristics that define how an individual is, memory, visual perception, arithmetic skills, language, praxias and executive function, and, on the other hand, personality, which is the set of characteristics that define what a person is like, where the MMPI-2 will be used, in order to assess personality and psychological disorders in patients with substance abuse. The objective of this research was to analyze the neuropsychological profile and personality traits of patients with addictions. The methodology used was qualitative, a case analysis design and descriptive in scope. Interviews with four individuals were used, in addition to the application of the third edition of the Neuropsi, attention and memory, and the MMPI-2. Based on the most relevant results, the existence of severe impairment was corroborated, especially in areas such as memory, while, with regard to personality, a common pattern was observed among the participants, highlighting the existence of social introversion and difficulties in maintaining stable relationships. Therefore, this study concludes that long-term drug addiction generates severe alterations in memory, attention and executive functions, as well as personality patterns that influence substance use
Las adicciones son trastornos complejos, donde un individuo es dependiente a una acción o sustancia, generando diversos problemas en la vida diaria del individuo, tanto a nivel fisiológico, como neurológico, por esto, es que se analizara el perfil neuropsicológico, el cual es una evaluación con la cual se podrán analizar diversas funciones neurológicas, como viene siendo la atención, la memoria, la percepción visual, las habilidades aritméticas, el lenguaje, las praxias y la función ejecutiva, y, por otro lado, la personalidad, la cual es el conjunto de características que definen el cómo es una persona, donde se utilizara el MMPI-2, con la finalidad de evaluar la personalidad y los trastornos psicológicos dentro de los pacientes por consumo de sustancias. La presente investigación tuvo como objetivo el analizar el perfil neuropsicológico y los rasgos de personalidad de pacientes con adicciones. La metodología utilizada fue de tipo cualitativo, un diseño de análisis de caso y un alcance descriptivo. Se emplearon entrevistas a cuatro individuos, además de la aplicación de la tercera edición del Neuropsi, atención y memoria, y el MMPI-2. En base a los resultados más relevantes, se corrobora la existencia de alteración severa, sobre todo en apartados como la memoria, mientras que, en lo que respecta la personalidad, se observa un patrón en común dentro de los participantes, destacando la existencia de introversión social y dificultades para mantener relaciones estables. Por ello, este estudio concluye que la adicción a las drogas, a largo plazo generan alteraciones severas en lo que respecta la memoria, la atención y las funciones ejecutivas, además de patrones de personalidad que influyen en el consumo de sustancias.
Keywords: PSICOLOGÍA CLÍNICA; PERFIL NEUROPSICOLÓGICO; ADICCIÓN; PERSONALIDAD